Remote machining for laser cutting applications - Raja Mohd Salleh, Raja Bahtiar (2008)
Today CNC machines are essential for manufacturing companies. CNC machines increases production rate. CNC machines also decreases labour cost and energy consumption. However, CNC machines still have disadvantages. CNC machines today lack the ability of being able to operate whenever, wherever. That disadvantage limits production capabilities. To solve that problem, remote machining application was engineered. Remote machining is a process where a machine operator is able to operate the machine through teleoperation. Remote machine enables CNC machines to operate whenever wherever as long there is a local computer, the remote machine program and internet connection. The remote machine of this project consists of a server and a client program for control and a web camera for remote monitoring. This project is to apply remote machining on FKM’s laser cutting machine for machine upgrading and utilizing technology.